2021
DOI: 10.1080/07853890.2021.1900593
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of gut microbiota induces skeletal muscle atrophy by FXR-FGF15/19 signalling

Abstract: Background: Recent evidence indicates that host-gut microbiota crosstalk has nonnegligible effects on host skeletal muscle, yet gut microbiota-regulating mechanisms remain obscure. Methods: C57BL/6 mice were treated with a cocktail of antibiotics (Abx) to depress gut microbiota for 4 weeks. The profiles of gut microbiota and microbial bile acids were measured by 16S rRNA sequencing and ultra-performance liquid chromatography (UPLC), respectively. We performed qPCR, western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 66 publications
(46 reference statements)
0
41
0
Order By: Relevance
“…This muscle dysfunction was associated with an altered profile of BA that reaches the portal blood circulation. This change induces the inhibition of ileal FXR signaling with the consequent decrease in serum levels of FGF15, an enterokine related to muscle wasting [ 113 ]. Considering the antecedents related to muscular TGR5, BA, and sarcopenia [ 44 , 54 ], it is impossible to discard this receptor's participation in the muscle dysfunction associated with alteration in the microbiota-BA axis.…”
Section: Redox-dependent Mechanisms Participate In Damage Induced By Bile Acidsmentioning
confidence: 99%
“…This muscle dysfunction was associated with an altered profile of BA that reaches the portal blood circulation. This change induces the inhibition of ileal FXR signaling with the consequent decrease in serum levels of FGF15, an enterokine related to muscle wasting [ 113 ]. Considering the antecedents related to muscular TGR5, BA, and sarcopenia [ 44 , 54 ], it is impossible to discard this receptor's participation in the muscle dysfunction associated with alteration in the microbiota-BA axis.…”
Section: Redox-dependent Mechanisms Participate In Damage Induced By Bile Acidsmentioning
confidence: 99%
“…Although these authors found that streptomycin reduced muscle membrane permeability, it did not affect the amount of myofibre swelling using a dose 80-fold greater than that used in the current study (Hayao et al 2018). Most recently, Qiu and colleagues reported antibiotic-induced dysbiosis caused muscle atrophy which was shown to be mediated by a suppression of bile acid signalling to fibroblast growth factor 15; however, as with the aforementioned studies, these authors used antibiotic doses 100 time greater than those used in the current study (Qiu et al 2021). Finally, intraperitoneal injection of the antibiotic imipenem for five consecutive days did not affect muscle specific force (Owen et al 2019).…”
Section: Discussionmentioning
confidence: 54%
“…The changes in gut microbiota are involved with skeletal muscle mass by changing SCFA and inflammatory cytokines to modulate the gut-muscle axis. Qui et al used an antibiotic cocktail to mostly eliminate the gut microbiota of 10-week-old C57BL/6 mice and determine the effects on body composition [80]. The antibiotic-treated mice experienced skeletal muscle atrophy linked to decreased ileal farnesoid X receptor (FXR)-FGF15 signaling and subsequently impaired skeletal muscle protein synthesis.…”
Section: Gut Microbiota Sarcopenia and Gut-muscle Axismentioning
confidence: 99%